深海堆積物から分離した放線菌の生産するケラチナーゼと難分解性ケラチンの分解 - Imada, Chiaki; 今田, 千秋; イマダ, チアキ; 武本, 裕樹; Kobayashi, Takeshi; 小林, 武志; コバヤシ, タケシ; 寺原, 猛; 山田, 勝久 (海洋深層水利用学会, 2012)
鹿児島湾水深218mの海底堆積物から分離された放線菌のケラチナーゼ生産の培養条件を検討し、さらに培養液から本酵素を単離・精製して諸性状を明らかにした。高い酵素活性は1/4強度(25%,v/v)の人工海水濃度で見られた。培養液上清からイオン交換及びゲル濾過クロマトグラフィーによりケラチナーゼを精製して分子量が約3万で、熱及びpH安定性の高いことを確認した。 また,本粗酵素はカイメン,マダイのウロコ,羽毛および羊毛などの難分解性ケラチンを原型を留めないほど分解したが、アオウミガメの甲羅およびミンククジラのヒゲなどの難分解性ケラチンはほとんど分解しなかった。 Cultivation conditions for keratinase production by an actinomycete strain isolated from deep-sea sediments of Kagoshima Bay at a depth of 218 m were investigated and character ized. Maximum production of the enzyme was obtained in a quarter strength artificial seawater. Purified enzyme obtained from the culture supernatant of the strain using cation exchange chromatography and gel filtration showed an approximate molecular weight of 30,000D with thermostable and pH stable characteristics. Various native keratins such as sea sponge, scales of red seabream, feather and sheep wool were completely decomposed by the partially purified enzyme, whereas shell of green turtle and barbell of minke whale were hardly decomposed. journal article